Streptococcus pneumoniae serotypes and mortality in adults in South Africa: Analysis of national surveillance data (2003 - 2008) - Naidoo, Nireshni (My University, 2014)
Studies have shown an increased risk of mortality amongst adults with invasive pneumococcal disease (IPD) with certain serotypes but there are no data from South Africa. We aimed to determine the association between serotypes and in-hospital mortality among adults aged 15 years and older with IPD in South Africa. Methods IPD cases were identified through the GERMS-SA national laboratory-based surveillance programme. Patient data from 25 enhanced surveillance sites from 2003-2008 (pre-pneumococcal conjugate vaccine introduction) with available data on serotype and in-hospital outcome were used. We assessed the association between the 20 most common serotypes and mortality among patients ≥15 years of age using univariate and multivariable logistic regression models. Results From January 2003 through December 2008, there were 3953 cases of IPD amongst adults older than 15 years of age meeting the study inclusion criteria. Amongst the 20 commonest serotypes, the incidence of serotypes 4, 19A, 23F and 18C increased significantly, and serotypes 1, 25 and 5 decreased significantly from 2003 to 2008. Serotype 1 was the commonest serotype overall (16%, 651/3953), followed by serotype 19A (11%, 443/3953) and serotype 4 (7%, 289/3953). The case-fatality ratio (CFR) was 55% (641/1166) for meningitis and 23% (576/2484) for bacteremia (p<0.001). Serotype 19F had the highest CFR of 48% (100/207), followed by 39% (99/252) for serotype 23F and 38% (246/651) for serotype 1. On multivariable analysis, factors independently associated with mortality were disease caused by serotypes 1 (OR 1.93, 95% CI 1.05–3.53) and 19F (OR 2.89, 95% CI 1.38–6.06) compared to serotype 4; increasing age (25-44 years, OR 1.75, 95% CI 1.03–2.95; 45-64 years, OR 3.56, 95% CI 2.00–6.35; ≥65 years, OR 5.17, 95% CI 1.89–14.14; compared to 15-24 years); living in provinces with intermediate (OR 1.65, 95% CI 1.16–2.35) or high poverty rates (OR 1.72, 95% CI 1.02–2.92) compared to provinces with low poverty rates; having meningitis (OR 4.07, 95% CI 2.98–5.55) compared to bacteremia; prior antibiotic treatment in the last two months (OR 3.93, 95% CI 2.50–6.20); inappropriate antibiotic treatment (OR 2.37, 95% CI 1.74–3.22) and positive HIV status (OR 1.69, 95% CI 1.04–2.75). Conclusion Serotypes associated with increased mortality are included in the 10-and-13-valent pneumococcal conjugate vaccine and may be expected to become less common in adults as a result of indirect effects following routine immunization in infants. HIV-infected adults experience increased mortality and the more widespread availability of antiretroviral therapy is likely to substantially improve the quality of life of HIV-infected individuals in terms of physical and mental health and decrease the incidence of IPD and therefore mortality.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Epidemiology in the field of Epidemiology & Biostatistics January 2014
Keywords: Pneumococcal Infections